Penjadwalan Pekerjaan pada No-Wait Flowshop dengan Kriteria Minimasi Total Waktu Tinggal Aktual Menggunakan Algoritma Genetik - Urip Sarwo Sambodo; Yuniaristanto -; Cucuk Nur Rosyidi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2003)
This research uses genetic algorithm for no-wait flowshop scheduling problem. The shop requires the condition that each job be processed without any interruptions on all m machines and between two consecutive machine. This means that the start of processing a job on a given machine may be delayed in order to make the completion of the job on the machine coincide with this beginning of processing the job on the subsequent machine. The objective for the model is to minimize total actual flow time accommodating the condition that job to be processed arrive at the shop at any times when needed and the condition that the completed job be delivered at a common due-date. Genetic algorithm is randomly and structured search to find optimal solution. Numerical experience shows that for a given scheduling problem, genetic algorithm solution better than before (Yuniaristanto, 2001)